Investigating the validation, reliability and usability of automated method for testing auditory sensitivity (AMTAS) with malay instructional video in clinical and non-clinical settings - Hatta, Nor Hidayah Mohammed (2025)
The Automated Method for Testing Auditory Sensitivity (AMTAS) is a self-administered hearing assessment tool that utilizes a tablet, headphones, and AMTAS software to determine hearing thresholds. While AMTAS has been validated internationally for over two decades and has shown strong potential, such research has never been conducted in Malaysia. This study aimed to assess the validity, reliability, and usability of AMTAS with a Malay instructional video among Malaysian adults through three phases. Phase I involved the verbatim translation of AMTAS instructional video and face validation of the Malay version of the mHealth App Usability Questionnaire (M-MAUQ). Based on responses from 30 participants (mean age = 45.62 ± 14.13 years), the face validity index (FVI) was 0.98 for both Item-FVI and Scale-FVI, indicating excellent clarity and comprehensibility. Phase II, conducted in clinical settings at Hospital Tuanku Ja’afar Seremban (HTJS) and Hospital Rembau (HR), assessed validity by comparing AMTAS and pure-tone audiometry (PTA) thresholds, reliability through AMTAS test-retest measurements, and usability using M-MAUQ. A total of 100 participants (mean age 44.72 ± 14.13) underwent validation testing, while 30 participants (mean age 44.43 ± 14.63) participated in reliability testing. All 130 participants were included in the usability testing. For validity, the mean difference between AMTAS and PTA thresholds ranged from 0.30 dB HL to 3.40 dB HL, with over 95% of results within an acceptable ±10 dB difference. Agreement in hearing loss severity between AMTAS and PTA was high (Kappa = 0.95-0.96). Reliability demonstrated good consistency across all frequencies with intraclass correlation coefficient (ICC) ranged from 0.64 to 0.99. Phase III replicated Phase II in a non-clinical setting at a community centre, involving 22 participants for validation (mean age = 27.41 ± 7.92) and 15 for reliability (mean age = 26.82 ± 8.29). The mean difference between AMTAS and PTA thresholds ranged from 3.18 dB HL to 7.50 dB HL, with strong reliability (ICC > 0.80). Usability showed high ratings in both Phase II and III, with mean scores exceeding 6.0 (out of 7.0) across all domains, reflecting high user satisfaction and feasibility. AMTAS testing was also significantly faster than PTA, reducing test time by an average of 3.03 minutes per person in clinical settings and 2.68 minutes in non-clinical settings. In conclusion, AMTAS meets the standards of conventional PTA in terms of validity, reliability, and usability, supporting its potential for wider use in clinical and non-clinical settings among the Malaysian population